YACON PERSPECTIVE VEGETABLE CULTURE FOR UZBEKISTAN - Akramov Umidilla Ikramjanovich; Davlatov Khikmatilla Rakhmatillo ugli (International Engineering Journal For Research & Development, 2020)
In Uzbekistan, large-scale measures have been taken recently to ensure food security and fully meet the needs of the population for vegetable products, as well as expand their assortments. However, the range of vegetables in Uzbekistan is insufficient and needs to be expanded. The article presents the results of the morphological properties, productivity and chemical composition of the root tubers of Yacon during the introduction of the soil-climatic condition of Uzbekistan. The mass of the largest large root tubers was 270 g, large - 95 g, medium - 70 g, and small - 35 g, the yield of root tubers in the bush - 2.5 kg.